Korelasi antara Perkembangan Motorik Halus dan Keterampilan Pra Menulis Anak - Wahyuni, Desvi; Aprillia, Elisa; Febrianti; Fauzi, Muhammad (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
This study aims to see the relationship between fine motor development and pre-writing skills in children aged 4-5. This study uses a quantitative approach in the form of correlation involving 45 children aged 4-5 years in Kindergarten X Palembang. Data collection in the study in the form of observation, questionnaires, and documentation was analyzed using SPPS version 29 to test validity, reliability, normality test, linearity test, and hypothesis test. From the calculation obtained, the value of r count = (0.343), while df = n (45) -2 = 43 with a significant level (0.05). The calculation obtained, r count > r table, shows a relationship between the two variables tested. Following the criteria for hypothesis testing, namely r count > r table, Ha is accepted and Ho is rejected. So it can be concluded that there is a relationship between fine motor development and pre-writing skills there is a relationship between fine motor development and pre-writing skills of children aged 4-5 years in Kindergarten X Palembang.